Arbuscular mycorrhizal colonization of vascular plants from the Yungas forests, Argentina - Becerra, Alejandra Gabriela (2007)
In Argentina, the Yungas forests are among the ecosystems most affected by human activity, with loss of biodiversity. To assess the mycorrhizal status in these ecosystems, the roots of 41 native plant species belonging to 25 families were collected throughout the year from two sites of the Yungas forests. Roots were washed and stained to study the presence of arbuscular mycorrhizas (AM). Morphological types of arbuscular mycorrhizas (Arum and Paris-type) and colonization patterns were identified and photographed. All plants presented AM colonization. The AM colonization patterns varied from single intracellular aseptate hyphae, coils, appresoria, to vesicles and/or arbuscules. Among the species studied, the Paris-type colonization showed to be dominant. Results confirmed that AM hosts are predominant in the Yungas of South American forests.